International crime data collection: Priorities for the United Nations - Alvazzi del Frate, Anna (Improving knowledge on crime, 2009)
The challenge of collecting crime statistics that can be used in cross-national comparisons has faced the international community for over 150 years. While some form of administrative police statistics are generated in almost every country, criminologists and statisticians have long recognized the limitations such statistics as proxies for the measurement of crime. Different legal systems, capacities and methods of recording crime further complicate the cross-national comparison of figures. The author of the present article examines ways forward for international crime data collection, including innovative solutions such as crime victim surveys, and summarizes the proposals made at the meeting of the open-ended expert group on ways and means of improving crime data collection research and analysis with a view to enhancing the work of the United Nations Office on Drugs and Crime and other relevant entities, held in Vienna from 8 to 10 February 2006. Information can be a valuable driver of change. It shines a light on any society. It can foster awareness and understanding of social injustices and it can provide evidence for people both within and outside government to argue for, to decide on and to implement successful reforms. Information is the lifeblood of transparent, informed and open societies fundamental aspects of democratic and wellmanaged States [1].